Model spasial daerah potensi banjir rob di pesisir Kabupaten Sukabumi Jawa Barat - Ankiq Taofiqurohman S (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2012)
Abstract. On March 2012, the Coastal area of Kabupaten Sukabumi, West Java, was affected by tidal flooding. This tidal flooding occured because of the supermoon phenomenon that combine with heavy rains. The potential of tidal flood disaster in Kabupaten Sukabumi coastal area requires an immediate action in order to manage the disaster. The first step to mitigate the disaster is by mapping the area that potentially affected by tidal flood. The objective of this research is to modelling the tidal flood area in coastal of Kabupaten Sukabumi. The result of this research shows that the area that potentially affected by tidal flood without supermoon phenomenon is covering 29% of the coastal area of Kabupaten Sukabumi and it is increasing to 37% when supermoon phenomenon occured.